2015
DOI: 10.1155/2015/121895
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Structural Assessment of Ni(II) Complexes Derived from Bis(2-hydroxy-1-naphthaldehyde)succinoyldihydrazone

Abstract: The monometallic nickel(II) complexes [Ni(H2nsh)(A)2]·nH2O (where A = water (H2O), n=0 (1); pyridine (py), n=2 (2); 2-picoline(2-pic), n=0 (3); 3-picoline(3-pic), n=2 (4); and 4-picoline(4-pic), n=0 (5)) and homobimetallic nickel(II) complexes [Ni2(nsh)(A)4]·nH2O (where A = water (H2O), n=1 (6); pyridine (py), n=4 (7); 2-picoline(2-pic), n=4 (8); 3-picoline(3-pic), n=4 (9); and 4-picoline(4-pic), n=4 (10), resp.) have been synthesized in methanol from bis(2-hydroxy-1-naphthaldehyde)succinoyldihydrazone (H4nsh)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Moreover, the ligands showed absorption maxima in the range of 300-370 nm which ascribed to (n→π * ) transition for the loan pair of electrons on the hetero atom of (>C=O) and (-N=CH-) moieties. During formation of the complexes, the (π→π * ) transition shifted slightly towards longer wave length, whereas the (n→π * ) transition of (>C=O) and (-N=CH-) largely shifted to the longer wave lengths, suggesting the chelation of the ligands to the metal center [18]. The complexes did not show any d-d electronic transition due to completely filled d 10 electronic configuration of cadmium ion [19].…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the ligands showed absorption maxima in the range of 300-370 nm which ascribed to (n→π * ) transition for the loan pair of electrons on the hetero atom of (>C=O) and (-N=CH-) moieties. During formation of the complexes, the (π→π * ) transition shifted slightly towards longer wave length, whereas the (n→π * ) transition of (>C=O) and (-N=CH-) largely shifted to the longer wave lengths, suggesting the chelation of the ligands to the metal center [18]. The complexes did not show any d-d electronic transition due to completely filled d 10 electronic configuration of cadmium ion [19].…”
Section: Resultsmentioning
confidence: 91%
“…Initially, the UV-vis analysis of Cd-MOF 1 showed the highest absorption (λ max ) at 323 nm, possibly due to the n-π* or π-π* transitions in the 'strut' ATA (Fig. S12 †) 40,41 After post-synthetic modifications, a bathochromic shift (∼10 nm, Fig. S12 †) was observed in the absorption band owing to N-functionalization with the incorporation of conjugated aromatic entities in the MOF skeleton.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…The coordination number of these compounds was either six or nine relying upon the anionic ligand [62]. Chakrabarty et al [63] investigated the synthesis and characterization of some nickel complexes as mono and homo dimetallic derived from bis(2-hydroxynaphthalene-1-carbaldehyde)succinoyldihydrazone (Fig. 15).They observed that the complexes with mono nickel have octahedral geometry while complexes with bi-nickels have deformed octahedral geometry in which one of the nickel lopes is available in N2O2 coordination circle and another nickel focus is bind to it through oxygen of phenolate.…”
Section: Complexes Of 2-hydroxynaphthalene-1-carbaldehyde Azomethine mentioning
confidence: 99%